AAML0523: A report from the Children's Oncology Group on the efficacy of clofarabine in combination with cytarabine in pediatric patients with recurrent acute myeloid leukemia. Issue 16 (25th April 2014) - Cooper, Todd M.; Alonzo, Todd A.; Gerbing, Robert B.; Perentesis, John P.; Whitlock, James A.; Taub, Jeffrey W.; Horton, Terzah M.; Gamis, Alan S.; Meshinchi, Soheil; Loken, Michael R.; Razzouk, Bassem I.
Abstract : BACKGROUND: The discovery of new, effective non–anthracycline‐based reinduction regimens for children with recurrent acute myeloid leukemia (AML) is critical. In this phase 1/2 study, the tolerability and overall response rate of clofarabine in combination with cytarabine was investigated in children with recurrent/refractory AML. METHODS: AAML0523 enrolled 49 children with AML in first recurrence or who were refractory to induction therapy. The study consisted of a dose‐finding phase (9 patients) and an efficacy phase (40 patients). Two children received clofarabine at a dose of 40 mg/m 2 /day and 47 children at a dose of 52 mg/m 2 /day. RESULTS: Toxicities typical for intensive chemotherapy regimens were observed at all doses of clofarabine. The recommended pediatric phase 2 dose of clofarabine in combination with cytarabine was 52 mg/m 2 /day for 5 days. Of 48 evaluable patients, the overall response rate (complete remission plus complete remission with partial platelet recovery) was 48%. Four patients met conventional criteria for complete remission with incomplete count recovery. Twenty‐one of 23 responders subsequently underwent hematopoietic stem cell transplantation. The overall survival rate at 3 years was 46% for responders compared with 16% for nonresponders ( P  < .001). Patients found to have no minimal residual disease at the end of the first cycle by flow cytometric analysis had superior overall survival after 1 year (100% vs 38%; P  = .01). CONCLUSIONS: The combination of clofarabine and cytarabine yielded an acceptable response rate without excess toxicity in children with recurrent AML. The nearly 50% survival rate reported in responders is highly encouraging in these high‐risk patients and suggests that this combination is an effective bridge to hematopoietic stem cell transplantation. Cancer 2014;120:2482–2489. © 2014 American Cancer Society . Abstract : The Children's Oncology Group conducted a phase 1/2 study, AAML0523, to determine the tolerability and overall response rate of clofarabine in combination with cytarabine in children with recurrent/refractory acute myeloid leukemia. The combination yielded an acceptable response rate without excess toxicity, and survival rates in responders suggest that this combination is an effective bridge to hematopoietic stem cell transplantation.